Adaptive Assessment Tools for Language Learners: A Review of Current Technologies - Cahyati, Sri Supiah; Iqbal, Kiran; Malik, Fatima (Journal International of Lingua and Technology, 2024)
In language education, adaptive assessment tools have emerged as valuable resources to address the diverse proficiency levels and learning needs of students. Traditional assessment methods often fail to capture the full range of learners’ skills, limiting personalized feedback and targeted support. Adaptive assessment technologies offer a solution by tailoring test content in real-time based on individual responses, providing a more accurate and dynamic measure of language proficiency. This research aims to review current adaptive assessment technologies in language education, examining their functionalities, benefits, and limitations. A comprehensive literature review was conducted, analyzing recent studies and technology reports on various adaptive assessment tools used in language learning. The research focuses on key features such as real-time adaptability, personalized feedback, and skill-specific assessments. The tools reviewed include applications designed for different language skills, such as reading, writing, listening, and speaking, and their effectiveness was evaluated based on learner engagement, accuracy, and pedagogical value. Findings indicate that adaptive assessment tools improve learner motivation and engagement by adjusting the difficulty level to match individual abilities. Additionally, these tools provide more targeted insights for educators, enabling personalized instruction. However, challenges remain, including the high cost of implementation and the need for technical training for educators. These findings highlight the potential of adaptive assessments to enhance language learning but underscore the need for further development to make them more accessible. This review concludes that adaptive assessment tools are transformative in language education, though efforts are needed to address cost and accessibility challenges. Further research should focus on refining these tools and exploring their long-term impact on language proficiency.